Three-dimensional porous MXene-cellulose aerogel: An efficient adsorbent for sequential capture of Hg(II) and decolorization of methylene blue - Ming Li; Xiaofei Fan; Jianing Hu; Jinghong Zhang; Huining Xiao; Yuling Zhang (Desalination, 2026)

Suitable particle-size biochar enhances resilience of potato production and soil environmental to irregular precipitation in semiarid region - Zhaoyang Li; Nan Shi; Zhimin Yang; Yubo Cao; Shimeng Fan; Musawer Abbas; Weixing Shan; Ansabayeva Assiya; Zhikuan Jia; Enke Liu; Kadambot H.M. Siddique; Ruixia Ding; et al. (Bioresource Technology, 2026)

Mussel-inspired engineering of green spherical cellulose adsorbents with PEI/PDA multilayers for efficient and selective mercury capture - Ming Li; Yuxin Gong; Xiaofei Fan; Jianing Hu; Shiwei Guo; Yuling Zhang; Huining Xiao (Desalination, 2026)

Explainable machine learning-based study on the applicability of thermal indicators for university classrooms in summer - Luyao Wang; Fan Fei; Yan Wang; Yongwei Song; Yuling Xiao; Weidong Wu; Kunkun Zhao; Hiroatsu Fukuda (Building and Environment, 2026)

Novel inter-cable wire rope dampers for hanger cable vibration control: Experiment, FE modeling method, and Field test - Shilong Yang; Keyu Lai; Wei Fan; Yuling Liu; Zhiheng Chen; Zhengqing Chen (Engineering Structures, 2026)

Characteristics and Mechanisms of Crack Propagation in Gas-Bearing Coal Under Adsorptive Versus Non-Adsorptive Gas Conditions - Dengke Wang; Yixuan Tang; Wenrui Li; Hongtu Zhang; Biao He; Furu Kang; Shixing Fan; Baisheng Nie; Yuling Xia; Xiaofei Pang; Jinhao Yu (Natural Resources Research, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Integrated metabolomics to systematically monitor quality indicators and metabolic dynamics in stored Ophiocordyceps sinensis - Chuyu Tang; Yuejun Fan; Bing Jia; Haoxu Tang; Yuling Li; Xiuzhang Li (Food Chemistry, 2026)

Adjusting fertilization depth for sustainable potato production in arid and semi-arid regions - Zhaoyang Li; Yukang Wang; Nan Shi; Yixuan Yuan; Lianjun Wei; Weixing Shan; Medelbek Meruyert; Ansabayeva Assiya; Zhikuan Jia; Kadambot H.M. Siddique; Ruixia Ding; Peng Wu; et al. (Field Crops Research, 2026)

Warming‐Induced Carbon Vulnerability in Permafrost Forests: A Shift in Q 10 From Continuous to Discontinuous Zones - Changjiang Huang; Tadeo Sáez‐Sandino; Guiyao Zhou; Lingyan Zhou; Tongyao Kong; Yuling Fu; Hongyang Chen; Yimin Zhu; Shuying Qiu; Kui Xue; Chongwei Fan; Lei Cao; et al. (Global Change Biology, 2026)
Permafrost forests harbor vast, climate‐sensitive carbon (C) reservoirs whose vulnerability largely depends on temperature sensitivity of microbial respiration ( Q 10 ). However, substantial uncertainties persist in predicting Q 10 patterns due to complex interactions among multiple ecological factors. Here, we conducted a standardized field survey with controlled incubations across a regional gradient from continuous permafrost (CP) and discontinuous permafrost (Dis‐CP, including sporadic and isolated ones) in the Greater Khingan Mountains to quantify Q 10 values and identify their main ecological controls. We found that the Q 10 values were significantly higher in CP than Dis‐CP forests, indicating a stronger microbial respiratory response to warming in the coldest permafrost regions. Statistical analysis revealed that the soil microbiome was the most important factor explaining Q 10 values in CP forest (47.8%), whereas a distinct set of factors (plant production, fine texture, substrate quality, and mean annual ground temperature) explained the largest proportion (63.2%) of Q 10 variation in Dis‐CP forests. Our findings suggest that warming‐induced permafrost degradation is likely to shift the dominant controls for Q 10 from microbial community to abiotic and plant‐related factors, while enhancing greenhouse gas emissions from permafrost soils.

Molecular design of polyoxovanadate cathodes for advanced AZIBs: Multielectron redox chemistry and structural engineering - Yu Zhang; Tiantian Guan; Fan Yang; Qing Han; Lingling Xie; Xuejing Qiu; Lei Wang; Hongjun Chen; Yuling Wang; Xiaobo Ji; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Mitochondria-targeted NIR fluorescent probe for detection of hydrogen sulfide and its application in monitoring food freshness and bioimaging - Yiyan Huang; Zhengkuan Tan; Xiaoyu Zhang; Haichang Ding; Jing Zhang; Chunmei Jian; Yuling Zeng; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

A high-static-low-dynamic stiffness wire rope isolator with a magnetic negative stiffness device: Experiment, analytical method, and optimization - Shilong Yang; Wei Fan; Yuling Liu; Lingfei Ma; Zhengqing Chen (Engineering Structures, 2025)

Endogenous stem cell repair strategy via electromechanical interaction for stress injury - Honglin Xiang; Fan Wang; Qing Zhang; Zeyu Han; Yefei Lei; Neng Lai; Ke Jiang; Hanfeng Yang; Wenguo Cui; Yuling Li (Chemical Engineering Journal, 2025)

Lactobacillus plantarum LP104 improved intestinal and brain inflammation by modulating TLR4 pathway and gut flora in alcohol liver injury mice - Yue Zhang; Yuxuan Ma; Yuling Fan; Yuexin Gao; Yamei He; Yu Wang; Bo Nan; Jingsheng Liu; Xia Li; Yuhua Wang (Food Bioscience, 2024)

Design, construction and evaluation of collaborative bio-system of Vibrio fluvialis with Chlorella sorokiniana for treating actual printing and dyeing wastewater - Yuling Song; Lijun Wang; Xi Qiang; Menglin Guo; Wenhui Gu; Songcui Wu; Shan Gao; Xuehua Liu; Xiujun Xie; Quancheng Fan; Jing Zhang; Zengling Ma; et al. (Chemical Engineering Journal, 2024)

Enhanced generation and effective utilization of H2O2 for simultaneous aging of plastics in the C3N4/Vis-LED system with the addition of phenol - Xiaoman Zhang; Ting Zhang; Hongyang Guo; Shuqi Wan; Xiaodan Liu; Jianhui Sun; Yuling Zhao; Shuying Dong; Xianfa Su; Maohong Fan (Chemical Engineering Journal, 2024)

Synergistic effect of Ru single atoms and MnO2 to boost oxygen reduction/evolution activity via strong electronic interaction - Shan Liu; Taotao Zeng; Zhanglong He; Mingqing Zuo; Shuguang Chen; Yuling Liu; Zheqiong Fan; Hao He; Qingyu Kong; Zeyan Zhou; Lei Han (Chemical Engineering Journal, 2024)

A turn-off xanthene-based fluorescent probe for detection of cysteine and its practical application in bioimaging and food samples - Na Tang; Kangshuo Xu; Ruian Sun; Haichang Ding; Yuling Zeng; Yuan Ji; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2024)

A novel approach for quantifying the influence intensity of urban water and greenery resources on microclimate for efficient utilization - Fan Fei; Yuling Xiao; Luyao Wang; Yan Wang; Hiroatsu Fukuda; Wanxiang Yao; Haiming Yu; Qiwei Dong (Sustainable Cities and Society, 2024)

Salicylic acid-mediated alleviation of salt stress: Insights from physiological and transcriptomic analysis in Asarum sieboldii Miq - Muhammad Haneef Kashif; Jiangxin Feng; Ruixian Dai; Yuling Fan; Yufei Xia; Zhong Liu (Chemosphere, 2024)

Responses of rice qualities to temperature and light in three different ecological environments in karst regions - Yuling Xia; Jianquan Qin; Ruike Huang; Fan Feng; Quanzhi Zhao; Xiaoyan Song (Journal of Cereal Science, 2024)

Neutral pH photoenzymatic activity of Au-doped g-C3N4 nanosheet for colorimetric detection of total antioxidant capacity in food samples - Xianming Li; Wentong Fan; Honghu Tang; Dongdong Li; Yuling Xiao; Bin Yang; Yi Zhao; Peng Wu (Food Chemistry, 2024)

The ameliorative effect of probiotics on diet-induced lipid metabolism disorders: A review - Yu Wang; Zhiyi Ai; Xinyue Xing; Yuling Fan; Yue Zhang; Bo Nan; Xia Li; Yuhua Wang; Jingsheng Liu (Critical Reviews in Food Science and Nutrition, 2024)

Pd@HKUST-1@Cu(II)/CMC composite bead as an efficient synergistic bimetallic catalyst for Sonogashira cross-coupling reactions - Yuling Huang; Jiayi Huang; Yuping Zhou; Xuetao Fan; Yiqun Li (Carbohydrate Polymers, 2024)

Surface engineering based on element interdiffusion and interfacial reactions to boost the performance of LiCoO2 cathode material - Fanghui Du; Zhongxu Fan; Lei Ding; Yan Wang; Wenjing Shi; Jie Zhang; Hanyu Qu; Xiaoxuan Yu; Yuling Chen; Junwei Zheng (Chemical Engineering Journal, 2023)

Genome-Wide Identification, Evolution Analysis of PI-PLC Family and Their Expression Patterns in Response to Different Hormones and Growth in Banana (Musa L.) - Qiuzhen Wu; Zhengyang Fan; Feng Qi; Dan Li; Zihao Zhang; Yukun Chen; Yuji Huang; Yuling Lin; Zhongxiong Lai (Tropical Plant Biology, 2023)

A new method for evaluating the synergistic effect of urban water body and vegetation in the summer outdoor thermal environment - Fan Fei; Luyao Wang; Yan Wang; Wanxiang Yao; Hiroatsu Fukuda; Yuling Xiao; Lei Tian; Tongtong Ji (Journal of Cleaner Production, 2023)

Ameliorative effect of calcium poly(aspartic acid) (PASP-Ca) and calcium poly-γ-glutamic acid (γ-PGA-Ca) on soil acidity in different horizons - Fei Kang; Qilin Lv; Jingbiao Fan; Yun Zhang; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

The reaction mechanism of highly dispersed Cu atoms and ultrafine MnOx nanoclusters co-modified ZSM-5 based on in-situ heteronuclear substitution for catalytic oxidation C6H14 - Jian Li; Jingnan Hu; Yingjie Shi; Jiajia Zhao; Hongchang Wang; Shuang Deng; Yutao Cui; Fan Wang; Hongyan Long; Yuling Tan (Chemical Engineering Journal, 2023)

An interactive motion-tracking system for home-based assessing and training reach-to-target tasks in stroke survivors—a preliminary study - Wenke Fan; Yuling Zhang; Qing Mei Wang; Yulong Bai; Yi Wu (Medical & Biological Engineering & Computing, 2020)

CO 2 storage in coal to enhance coalbed methane recovery: a review of field experiments in China - Zhejun Pan; Jianping Ye; Fubao Zhou; Yuling Tan; Luke D. Connell; Jingjing Fan (International Geology Review, 2018)

Uncovering tea-specific secondary metabolism using transcriptomic and metabolomic analyses in grafts of Camellia sinensis and C. oleifera - Wei-Wei Deng; Jieyun Han; Yanbing Fan; Yuling Tai; Biying Zhu; Mengqian Lu; Rangjian Wang; Xiaochun Wan; Zheng-Zhu Zhang (Tree Genetics & Genomes, 2018)

A highly Selective Fluorescent Sensor for Monitoring Cu2+ Ion: Synthesis, Characterization and Photophysical Properties - Stephen Opeyemi Aderinto; Yuling Xu; Hongping Peng; Fei Wang; Huilu Wu; Xuyang Fan (Journal of Fluorescence, 2017)

Synthesis, Crystal Structures and Photo- and Electro-Luminescence of Copper(I) Complexes Containing Electron-Transporting Diaryl-1,3,4-Oxadiazole - Tianzhi Yu; Peng Liu; Haifang Chai; Jundan Kang; Yuling Zhao; Hui Zhang; Duowang Fan (Journal of Fluorescence, 2014)

Synthesis, Crystal Structure and Photoluminescence of a Cyclometalated Iridium(III) Coumarin Complex - Tianzhi Yu; Chengcheng Zhang; Yuling Zhao; ShaoQiang Guo; Peng Liu; Wentao Li; Duowang Fan (Journal of Fluorescence, 2013)

High-Efficiency Blue Electroluminescence Based on Coumarin Derivative 3-(4-(anthracen-10-yl)phenyl)-benzo[5,6]coumarin - Hui Zhang; Haifang Chai; Tianzhi Yu; Yuling Zhao; Duowang Fan (Journal of Fluorescence, 2012)

Synthesis, Photo- and Electro-Luminescence of 3-Benzoxazol-2-yl-Coumarin Derivatives - Yuling Zhao; Tianzhi Yu; Youzhi Wu; Hui Zhang; Duowang Fan; Zunwei Gan; Liangliang Yang; Xiaoqian Han; Yumei Zhang (Journal of Fluorescence, 2012)

Global genome expression analysis of rice in response to drought and high-salinity stresses in shoot, flag leaf, and panicle - Junli Zhou; Xiangfeng Wang; Yuling Jiao; Yonghua Qin; Xigang Liu; Kun He; Chen Chen; Ligeng Ma; Jian Wang; Lizhong Xiong; Qifa Zhang; Liumin Fan; et al. (Plant Molecular Biology, 2007)